Analysis of the correlation between vibrations and the number of shorted turns in the stator winding of a squirrel‑cage induction machine - Marczak, Mikołaj; Pietrowski, Wojciech; Górny, Konrad (Archives of Electrical Engineering (Online), 2025)
This paper presents a method of diagnosing a squirrel-cage induction motor based on the results of machine vibration analysis. The paper considers a fault involving an interturn short circuit in the winding of all phases of the stator. The waveforms of the diagnostic signals were recorded for selected configurations of winding shorts during steady state operation of the motor under constant torque load. In the next step of the study, wavelet packet decomposition was used to analyze the recorded waveforms of the vibration signals. The study focused on determining the correlation between the wavelet analysis results and the number of shorted turns. In addition, the effect of the wavelet used in the wavelet packet analysis on the correlation results was compared. As a result, a method was developed to detect shorted turns in the stator winding of an induction motor based on the results of wavelet packet analysis of the motor vibration.